2023
DOI: 10.1038/s41380-023-02203-y
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic dose, dopamine D2 receptor occupancy and extrapyramidal side-effects: a systematic review and dose-response meta-analysis

Abstract: Antipsychotic drugs differ in their propensity to cause extrapyramidal side-effects (EPS), but their dose-effects are unclear. Therefore, we conducted a systematic review and dose-response meta-analysis. We searched multiple electronic databases up to 20.02.2023 for fixed-dose studies investigating 16 second-generation antipsychotics and haloperidol (all formulations and administration routes) in adults with acute exacerbations of schizophrenia. The primary outcome was the number of participants receiving anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 72 publications
0
7
0
Order By: Relevance
“…Accordingly, our study examined the association between plasma cytokine concentrations during pregnancy and one month postpartum and depressive status one month postpartum. However, as pointed out in the paper by Kikuchi et al, 3 postpartum depression is observed with similar frequency even after 12 months. Therefore, it will be necessary to investigate long-term postpartum mood states and plasma cytokine concentrations, as pointed out by Veltre et al In previous reports, Corwin et al 4 measured cytokine levels (IL-6, IFN-γ, TNF-α, IL-1b, IL-10, IL-8) over time from 7 days through to 6 months (day 7, day 14, 1-, 2-, 3-and 6-month) postpartum, and compared these cytokine levels between postpartum women subgroups with EPDS greater than and less than 10.…”
Section: Disclosure Statementmentioning
confidence: 60%
See 1 more Smart Citation
“…Accordingly, our study examined the association between plasma cytokine concentrations during pregnancy and one month postpartum and depressive status one month postpartum. However, as pointed out in the paper by Kikuchi et al, 3 postpartum depression is observed with similar frequency even after 12 months. Therefore, it will be necessary to investigate long-term postpartum mood states and plasma cytokine concentrations, as pointed out by Veltre et al In previous reports, Corwin et al 4 measured cytokine levels (IL-6, IFN-γ, TNF-α, IL-1b, IL-10, IL-8) over time from 7 days through to 6 months (day 7, day 14, 1-, 2-, 3-and 6-month) postpartum, and compared these cytokine levels between postpartum women subgroups with EPDS greater than and less than 10.…”
Section: Disclosure Statementmentioning
confidence: 60%
“…2 Around 10% of patients taking brexpiprazole experienced EPS in clinical trials and research indicates that its risk for doses up to 3.4 mg is comparable to placebo. 2,3 This report presents a case of brexpiprazole-related tardive dystonia. Written informed consent was obtained from the patient for the publication of the details of her case.…”
mentioning
confidence: 99%
“…Correlations have been found between the dose of antipsychotic drugs and the incidence of adverse events. For example, the risk of extrapyramidal side effects increases dose‐dependently 11 . Second, empirical clinical studies suggest that East Asian patients may require lower dosages of psychotropic drugs, such as antipsychotics, lithium, and antidepressants, than non‐Asians 12 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, the risk of extrapyramidal side effects increases dose‐dependently. 11 Second, empirical clinical studies suggest that East Asian patients may require lower dosages of psychotropic drugs, such as antipsychotics, lithium, and antidepressants, than non‐Asians. 12 Racial and ethnic groups differ genetically in the activity of cytochrome P450, which participates in the metabolism of many drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Clozapine and olanzapine are associated with a higher risk of metabolic side effects [24], followed by the medium-risk drugs quetiapine and risperidone and the low-risk drugs ziprasidone and aripiprazole [25][26][27]. Furthermore, although less frequently than first-generation APs, atypical APs can also induce extrapyramidal side effects [28][29][30]. Although the exact underlying mechanisms of various adverse effects are not well understood, an increasing body of evidence has linked both typical and atypical APs to disturbed mitochondrial function [31,32].…”
Section: Introductionmentioning
confidence: 99%